Pengaruh Kualitas Pelayanan Posyandu Terhadap Kepuasan Ibu Balita di Posyandu Melati Mekar Desa Margajaya Kecamatan Ngamprah - Fitriyah, Anis; Fauziya, Fizi (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to determine the influence of service quality on the satisfaction of mothers with toddlers at Posyandu Melati Mekar RW 05, Margajaya Village, Ngamprah District, West Bandung Regency. The method used is a quantitative approach with data collected through questionnaires distributed to 70 respondents using a saturated sampling technique. The results showed that the service quality at Posyandu Melati Mekar was in the "very high" category with a score of 3,007 out of a maximum of 3,500, while the level of satisfaction among mothers was in the "high" category with a score of 2,900. The t test showed a t value of 9.592, which is greater than the t table value of 1.995, with a significance level of 0.001, indicating a significant influence of service quality on mother satisfaction. A correlation coefficient of 0.758 indicates a strong and positive relationship, while the determination coefficient of 57.5% shows that service quality greatly contributes to customer satisfaction. Thus, improving service quality can directly increase user satisfaction with posyandu services